Scheme of arrangement (SOA) in the rehabilitation of abandoned housing projects: A case study Of Malaysia - Md Dahlan, Nuarrual Hilal (The International Center for Research & Development, 2013)
If a company is insolvent and is unable to pay its debts. it may be subject to a schenie of arrangement (SOA) on the application of the creditors or members or the liquidator or the company itself.The usual purpose of SOA is for the SOA manager to take over the affairs and business of a debtor insolvent company in order to settle off the debts of the creditors and once all the debts are fully paid, the control of the debt or insolvent company will be handed over back to the previous management.The SOA manager is armed with certain powers and duties in the SOA administration.The benefit of obtaining SOA is to give some time to the SOA manager to run the debtor insolvent company in order to settle its debts.Moratoriutri power will be given to SOA Manager against any actions and proceedings by the creditors in the course of the SOA administration.This ~noratoriurii power is to allow the SOA manager to exercise the SOA effectively without any interference by the creditors and the members of the debtor insolvent company.In respect of insolvent housing developer company which becomes subject to SOA, similar duties are carried out by the appointed SOA manager,viz to take over the affairs of the company, to settle off all the debts of the creditors. to carry on any project and business left by the company if this is expedient in accordance with the law and the wish of the creditors or the members.Once all these have been dispensed with, the affairs and management of the company will be handed back to the previous management.